The Effect of Involvement in a Student-run Free Clinic Project on Attitudes toward the Underserved and Interest in Primary Care - Smith, Sunny D. (J Health Care Poor Underserved, 2014)
METHODS: The authors designed a survey instrument to examine the effect of involvement in a student-run free clinic project (SRFCP) on medical student self-reported attitudes toward the underserved and interest in primary care. From 2001–2010, first- and second-year medical students in an introductory service-learning elective course rated each of 15 statements on a seven-point Likert scale pre/post survey. Wilcoxon’s signed rank test was performed on all matched pairs and an intent-to-treat analysis included unmatched pairs. RESULTS: The response rate was 97.9%, with 914 of 934 students enrolled participating. Significant increases were seen in each of the 15 items in matched pre/post survey pairs, N = 433 (47.4%), or with an intent-to-treat analysis, N = 914 (p ≤ .002 for all). CONCLUSIONS: This study found that medical student involvement in a SRFCP improved student knowledge, skills, attitudes and self-efficacy with the underserved, interest in work with the underserved after graduation, and interest in primary care.